The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1103/physreve.99.062704
|View full text |Cite
|
Sign up to set email alerts
|

Metastable room-temperature twist-bend nematic phases via photopolymerization

Abstract: This is a repository copy of Metastable room-temperature twist-bend nematic phases via photopolymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In sealed cells, however, 8CB/CB7CB mixtures in the range 40 wt % < φ < 55 wt % exhibited room temperature N TB phases that were observed to be metastable for at least 6 months in XRD capillaries and optical cells. It should be noted that, if other studies have already reported low temperature N TB phases in mixtures [16][17][18]47], many of them tend to rapidly crystallize at room temperature [20]. This feature allowed us to characterize the 8CB/CB7CB system in detail.…”
Section: Phase Diagramsmentioning
confidence: 87%
“…In sealed cells, however, 8CB/CB7CB mixtures in the range 40 wt % < φ < 55 wt % exhibited room temperature N TB phases that were observed to be metastable for at least 6 months in XRD capillaries and optical cells. It should be noted that, if other studies have already reported low temperature N TB phases in mixtures [16][17][18]47], many of them tend to rapidly crystallize at room temperature [20]. This feature allowed us to characterize the 8CB/CB7CB system in detail.…”
Section: Phase Diagramsmentioning
confidence: 87%
“…33 Scanning electron microscopy observations of the photo-crosslinked samples of the N TB phase revealed a helical organization of the nanostructures. [34][35][36] In addition to the N TB phase, other structurally associated mesophases, such as heliconical smectic (Sm) phases based on bent-core molecules 37,38 and bent LC dimers, 39,40 the twist grain-boundary-twistbend nematic phase, 41 and the splay-bend N (N SB ) phase electrically induced from the N TB phase [42][43][44] have been experimentally verified. Furthermore, the splay N (N S ) phase with the modulation rotated 90° with respect to the N SB phase was discovered in some rod-like mesogens.…”
Section: Introductionmentioning
confidence: 99%
“…Using mixtures with other mesogens is a useful method to lower the N-N TB phase-transition temperature, 18 ultimately achieving a metastable room temperature N TB phase 88 and its photocrosslinked state. 35 However, the formation of room-temperature N TB materials from their single-component systems indeed remains a rarity. 50,61,64,67,68,70,72 This has restricted deep structural analyses and examination of the physical properties of the N TB phases, in addition to the development of new applications.…”
Section: Introductionmentioning
confidence: 99%
“…The latter observation was made with toroidal FCDs as well (Figure S2f, Supporting Information). To circumvent the longstanding issue of electric irreversibility of SmA FCDs, we build from prior studies of polymerization of LCs [ 8,22–24 ] and evaluate the ability of a new approach based on polymerization of SmA FCDs and electric reversibility of NLCs. To illustrate the potential of such an approach to increment new properties arising from the structure and organization of SmA FCDs with electric reversibility and dynamic adjustability, we use linear arrays of EHFCDs.…”
Section: Resultsmentioning
confidence: 99%
“…[ 13 ] Another way to reversibly switch or reconfigure SmA defect patterns consists in combining electric fields and thermal annealing from the N or isotropic (I) phases, [ 20,21 ] yet this again prevents from dynamic adjustability. Moreover, strategies like in situ polymerization of LCs, successfully applied to improve the physical properties of blue phase, [ 22 ] cholesteric, [ 23 ] and nematic structures, [ 8,24 ] have not been used to this end for SmA defect patterns so far.…”
Section: Introductionmentioning
confidence: 99%